Morphology of Koch Fractal Antenna - Mathur, Vinita; Gupta, Dr. Manisha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Antenna is paramount element for the radio communication entity using radio frequency and microwaves. In twenty-first century wireless communication systems, there is a demand for wider bandwidth, multiband and low profile antennas for both commercial and military purposes. This has initiated antenna analysis in various directions; one of them is using fractal shaped antenna elements. Fractal concepts have emerged and advanced as a unique technique for designing compact UWB antennas, because of the self-similarityand space-filling attributes. In a fractal antenna, the multiple frequencies of operation depend on the total dimensions of the design and the scale factor. There are varied fractal geometries that have been found to be favorable in developing novel and new models for antennas. In this paper we will be discussing one such type of fractal antennas i.e. the Koch structure. Koch antenna can be designed with a triangle, rectangle and pentagon as its initiator. Their geometry and parameters have been analyzed in this paper.